Sponsorship of television programs - Gan, Ser Hui (2015)
The emergence of sponsorship as a significant form of marketing communication is a comparatively recent development. In the last decade, commercial sponsorship in the UK has developed into a 190 million pound industry of growing significance and professionalism. In Singapore, more funds are expected to be channeled into the sponsorship industry as the population becomes more affluent and standard of living gets higher. However, it is television sponsorship which is likely to be the area of greatest sponsor attention. The growth of new media, such as cable and satellite television, and less restrictive legislation regarding broadcasting is likely to ensure the future growth of television sponsorship. This study explores the various factors behind sponsorship's dramatic growth and attempts to justify the huge expenditures invested.